2019
DOI: 10.3389/fvets.2019.00281
|View full text |Cite
|
Sign up to set email alerts
|

Keeping an Eye on Wild Brown Trout (Salmo trutta) Populations: Correlation Between Temperature, Environmental Parameters, and Proliferative Kidney Disease

Abstract: Proliferative kidney disease (PKD) is an emerging disease of salmonids caused by the myxozoan parasite Tetracapsuloides bryosalmonae , which plays a major role in the decrease of wild brown trout ( Salmo trutta ) populations in Switzerland. Strong evidence demonstrated that water temperature modulates parasite infection. However, less knowledge exists on how seasonal water temperature fluctuations influence PKD manifestation under field conditions, how further envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 72 publications
8
30
0
Order By: Relevance
“…In this study, the only two repeatedly sampled locations showed higher percentages of the examined fish displaying pathomorphological signs of PKD, along with greater numbers of samples tested positive for the presence of T. bryosalmonae using both IHC and qPCR in November, compared with the situation in April. Although the temperature in every sampling campaign presented was not optimal for the propagation of the parasite [ 43 ], the data confirmed the observed cycle of the infection in brown trout, with infection rates and pathoanatomical changes peaking in late summer [ 24 ], and a significant decline during cold temperature periods [ 25 , 27 ] when a partial or complete regeneration of renal tissue occurs [ 38 ]. To establish whether the reoccurring PKD symptoms in specific rivers are caused by reinfection of susceptible animals [ 38 ] or by a persistence of the parasite in clinically healthy fish [ 46 , 47 ] was beyond the scope of this study and would require additional repeated testing of selected locations.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In this study, the only two repeatedly sampled locations showed higher percentages of the examined fish displaying pathomorphological signs of PKD, along with greater numbers of samples tested positive for the presence of T. bryosalmonae using both IHC and qPCR in November, compared with the situation in April. Although the temperature in every sampling campaign presented was not optimal for the propagation of the parasite [ 43 ], the data confirmed the observed cycle of the infection in brown trout, with infection rates and pathoanatomical changes peaking in late summer [ 24 ], and a significant decline during cold temperature periods [ 25 , 27 ] when a partial or complete regeneration of renal tissue occurs [ 38 ]. To establish whether the reoccurring PKD symptoms in specific rivers are caused by reinfection of susceptible animals [ 38 ] or by a persistence of the parasite in clinically healthy fish [ 46 , 47 ] was beyond the scope of this study and would require additional repeated testing of selected locations.…”
Section: Discussionsupporting
confidence: 53%
“…Using histopathology and IHC, the PKD situation was best mapped in Switzerland, where T. bryosalmonae was found in 40–50% of the sampled rivers [ 41 , 42 , 43 ]. Studies on brown trout were also conducted in England (86% of rivers [ 44 ]) and Estonia (around 50% of rivers [ 45 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature driven PKD induced population decline is multifaceted, involving many indirect effects on survival (Burkhardt‐Holm & Zehnder, 2018). For example, PKD may make fish more susceptible to existing environmental stressors (Bruneaux et al., 2017) such as warmer than average summers (Borsuk et al., 2006; Hari set al., 2006; Rubin et al., 2019), pollution (Bailey et al., 2018), or secondary infection with other pathogens (Arndt et al., 2019; Chilmonczyk et al., 2002; Hedrick et al., 1993). PKD compromised condition (Bruneaux et al., 2017) could potentially decrease survival through subsequent metabolic challenging periods like winter (recruitment) or migration (Kent et al., 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The current 51.9% decrease in brown trout density in the Wutach in the last decade is suggestive of a recent upstream spread of T. bryosalmonae . The pending increase in temperatures due to climate change make it increasingly essential for surviving salmonid populations in rivers such as the Wutach to have secure access to head waters, small tributaries or other areas with relatively cool and well oxygenated water, where the effects of T. bryosalmonae infection tend to be mild (Rubin et al., 2019; Strepparava et al., 2018; Wahli et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation